2015
DOI: 10.1149/06908.0277ecst
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Germanium in Sulfuric Acid Based Solutions

Abstract: The phenomenon and mechanism of germanium (hereinafter Ge) dissolution in sulfuric acid based solutions were studied. The sulfuric acid concentration, the presence of an oxidizer and the treatment time were varied as parameters of these tests. It was clarified that Ge surface is covered by two layers: germanium dioxide (hereinafter GeO2) and germanium monoxide (hereinafter GeO). GeO2 dissolves easily in water and in the sulfuric acid solutions with high water fraction. On the other hand, the dissolution of GeO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Ge wet etching with acidic H 2 O 2 has been adopted for a very long time, and the related mechanisms both on the nanoscale and the atomic scale have been extensively studied for the research associated with Ge surface passivation, Ge surface cleaning, and Ge wet etching processes , There are two different natural oxides, GeO and GeO 2 , on the surface of Ge . When H 2 O 2 was applied, the oxide which is primarily water-soluble GeO 2 will regrow.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ge wet etching with acidic H 2 O 2 has been adopted for a very long time, and the related mechanisms both on the nanoscale and the atomic scale have been extensively studied for the research associated with Ge surface passivation, Ge surface cleaning, and Ge wet etching processes , There are two different natural oxides, GeO and GeO 2 , on the surface of Ge . When H 2 O 2 was applied, the oxide which is primarily water-soluble GeO 2 will regrow.…”
Section: Results and Discussionmentioning
confidence: 99%
“… 38 32 , 39 There are two different natural oxides, GeO and GeO 2 , on the surface of Ge. 40 When H 2 O 2 was applied, the oxide which is primarily water-soluble GeO 2 will regrow. This oxide dissolves slowly in H 2 O and can be removed more rapidly by acids.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This appears noteworthy given that the H300 thin film was fabricated from an A900 thin film via additional heat treatment at a lower temperature. However, the incorporation of H 2 O and the creation of hydrates may lead to the growth of the microstructure according to the chemical reactions given in Equation () and () [ 35,49,51,52 ] GeO 2 + H 2 normalO GeH 2 O 3 $$\left(\text{GeO}\right)_{2} \left(\text{+ H}\right)_{2} \text{O} \leftrightarrow \left(\text{GeH}\right)_{2} \left(\text{O}\right)_{3} \left(\right. \text{aq} \left.\right)$$ GeO 2 + 2H 2 O Ge ( OH ) 4 $$\left(\text{GeO}\right)_{2} \left(\text{+ 2H}\right)_{2} \text{O } \leftrightarrow \text{ Ge} \left(\left(\right.…”
Section: Resultsmentioning
confidence: 99%
“…This appears noteworthy given that the H300 thin film was fabricated from an A900 thin film via additional heat treatment at a lower temperature. However, the incorporation of H 2 O and the creation of hydrates may lead to the growth of the microstructure according to the chemical reactions given in Equation ( 3) and ( 4) [35,49,51,52]…”
Section: Solubilitymentioning
confidence: 99%
“…Further, the Ge 2 p 3/2 core‐level spectra from the KCN‐etched CZGTS (Ge/(Ge + Sn) = 0.2) reference sample is also included and the results indicate that a KCN etch treatment applied to the CZGTS absorber surface removes the Ge‐oxide species and leaves a clean surface with metal‐sulfide components only. It is not excluded that another treatment or water could actually remove the Ge‐oxide species at the surface of the absorber, since it was reported that GeO 2 is soluble in aqueous solutions, [ 25 ] but has not been studied in this work.…”
Section: Resultsmentioning
confidence: 99%